Group-living carpenter bees conserve heat and body mass better than solitary individuals in winter. (July 2022) - Ostwald, Madeleine M.; Fox, Trevor P.; Hillery, William S.; Shaffer, Zachary; Harrison, Jon F.; Fewell, Jennifer H.
Abstract : Environmental challenges are major drivers of the evolution of group living. In particular, harsh seasonal conditions can promote temporary or facultative social behaviour in primarily solitary animals. We asked how winter conditions might favour group living in a desert population of a facultatively social carpenter bee, Xylocopa sonorina Smith, that nests primarily in small groups during winter quiescence. We experimentally manipulated the social condition (social versus solitary) of bees living in observation nests in ambient winter conditions and measured effects of group living on temperature and body condition. Social bees experienced significantly warmer temperatures than solitary bees in identical nests. Furthermore, social bees experienced smaller reductions in body mass than solitary bees over the course of the 1-month observation period. These results suggest important benefits of group living in cold and resource-scarce conditions, which may allow X. sonorina to reduce risk of freezing and emerge from winter quiescence in better physiological condition. Seasonal associations such as these provide opportunities for extended social interactions among nestmates, an important context for the evolution of more complex cooperative behaviours. Highlights: Solitary bees lose more of their body mass than social bees in winter. Social bees are warmer than solitary bees at the coldest time of day. Combined physiological benefits may underlie social overwintering.